PENGEMBANGAN MULTIMEDIA PEMBELAJARAN AL-QUR’AN JUZ 30 BERBASIS MUROTTAL - Nur Cholid Cholid; Durrotul Muqoffa (Kopertais Wilayah X Jawa Tengah, 2020)
The development of instruksional multimedia is a technological ddvancement in the world of education. The existence of technological supprot in The field of Education makes teachers assisted in effort to improve the quality of learning and to achieve teaching objective. This study aim to determine : 1) how to make multimedia learning qur’an juz 30 based on murrotal; 2) determine the feasibility of murrotal-based Quran learning multimedia developed as a medium for learning the quran juz 30. This research is a research and development. This development research was carried out throught several stage, namely potential and problem, information gathering, products design, design validation, desain revision. In the validation stage, multimedia learning in the Quran si validated by material experts and media experts. Data collection techniques use are questionnaire for instrumen. The validation data is the converted to a likert scale to obtain a multimedia feasibility category based on murrotal Quran. This research and development has produced murrotal juz-based Quran learning video. Learning multimedia for Quran is feasible to be used in both good and very good categories. This can be seen in the result of validation of material experts with a score of 4.5 or the category of very good; validation of media experts with a score of 3.6 or good category.